Exploration of the Utilization of Lumio as Interactive Media in Science Learning in Elementary Schools - Hanip, Singgih Aulia; Gunansyah, Ganes; Prahani, Binar Kurnia (Journal of Innovation and Research in Primary Education, 2025)
This study aims to explore the use of Lumio as an interactive learning medium in Integrated Natural and Social Sciences (IPAS) subjects in elementary schools. This study uses a qualitative approach with an exploratory descriptive method which was carried out at SD Negeri 1 Suru, Nganjuk Regency, East Java. The research involved one science teacher and 28 grade V students, with data collection techniques through observation, semi-structured interviews, and documentation. The data collection process was conducted over a period of two weeks during the even semester of the 2024/2025 academic year. Data analysis was carried out using the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawing. The results showed that the use of Lumio increased students' active participation, strengthened the understanding of abstract IPAS concepts, and created a more collaborative learning atmosphere. Interactive features such as digital quizzes, concept mapping, and collaborative whiteboards have proven effective in facilitating meaningful learning. The teacher stated that Lumio helps the formative assessment process and speeds up the giving of feedback. The main obstacle faced is the limitation of devices and internet connections, but it can be overcome through teachers' adaptive strategies. This study recommends strengthening teacher capacity through educational technology training and the provision of adequate digital infrastructure. The findings support the implementation of the Independent Curriculum that encourages technology-based active learning. In conclusion, Lumio has great potential as an innovative medium that strengthens the integration of technology in science learning at the elementary school level.